Pesan Ramah dalam Meme Akun Instagram Jaringan Gusdurian dan Fihril (Kajian Pragmatik) - Rifa'atul Mahmudah (Institut Agama Islam Negeri Curup, 2018)
The recent memes are widely used in social media. Besides having an entertainment function, memes are a means of transmitting pleasant messages. Therefore, meme is much favored by social media users. However, the message contained in the meme is not directly (explicit), so in this study used implicature theory to find out the implicit messages. The memes are used from the instagram account @jaringangusdurian and @fihril, and taken five memes for analysis. The research method used is the note-taking method. The researcher first listens to the use of languages that contain phenomena of implicature. The data analysis method used is descriptive-analytic method. The data that the researcher has noted then the researcher describes in accordance with the disclosure of violations of cooperation maxims, description of implicature, and disclosure of the types of speech acts. From the analysis of memes, it can be concluded that; 1) help is about humanity (social) regardless of the attributes of religion, ethnicity and class, 2) as fellow human beings it is not appropriate to judge good and bad towards others based on their parameters of faith, because the duty of human beings is only to appreciate and respect each other, 3) more open and contextual in understanding friendly Islamic values for a dignified life, 4) about advising fellow humans is a good way. Even though the advice is true, it is still not justified in a non-friendly way. Keywords: friendly, meme, instagram, pragmatic.